2009
DOI: 10.1002/humu.20950
|View full text |Cite
|
Sign up to set email alerts
|

High frequency ofTARDBPgene mutations in Italian patients with amyotrophic lateral sclerosis

Abstract: Recent studies identified rare missense mutations in amyotrophic lateral sclerosis (ALS) patients in the TARDBP gene encoding TAR DNA binding protein (TDP)-43, the major protein of the ubiquitinated inclusions (UBIs) found in affected motor neurons (MNs). The aim of this study was to further define the spectrum of TARDBP mutations in a large cohort of 666 Italian ALS patients (125 familial and 541 sporadic cases). The entire coding region was sequenced in 281 patients, while in the remaining 385 cases only exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
170
5
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(186 citation statements)
references
References 40 publications
9
170
5
2
Order By: Relevance
“…Since it has also been published previously in controls, this substitution is likely to represent a non-pathogenic polymorphism (18,20,21). Novel synonymous SNPs were identified in 3 SALS cases in exon 2 (p.Leu27), exon 3 (p.Ser104) and exon 4 (p.Lys137), along with two SALS cases carrying the previously reported p.Ala66 SNP in exon 2 (18,21,23,(26)(27)(28).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Since it has also been published previously in controls, this substitution is likely to represent a non-pathogenic polymorphism (18,20,21). Novel synonymous SNPs were identified in 3 SALS cases in exon 2 (p.Leu27), exon 3 (p.Ser104) and exon 4 (p.Lys137), along with two SALS cases carrying the previously reported p.Ala66 SNP in exon 2 (18,21,23,(26)(27)(28).…”
Section: Resultssupporting
confidence: 57%
“…All our patients had clinical features in keeping with ALS and no mutations were found in patients with a pure lower MN clinical The familial p.Met337Val mutation has been identified in three other families with MND (20,23,28). In FALS1 (Met337Val) a marked intrafamilial variation in disease duration was observed, ranging from 9 months to 17 years.…”
Section: Broad Clinical Als Phenotypes Are Associated With Tardbp Mutmentioning
confidence: 60%
“…18 In the non-coding regions of TARDBP five genetic variations were detected, of which one (c.*208G4A) previously has been reported. 12 Segregation analyses were performed for c.*208G4A and c.543 þ 59A4G, and it suggested that neither is pathogenic.…”
Section: Novel Tardbp Mutations H-h Chiang Et Almentioning
confidence: 87%
“…This could be due to reduced penetrance of p.G357R, which is in agreement with other reported TARDBP mutations. [8][9][10][11][12]18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation